As aulas de matemática nos anos iniciais e a integração das tecnologias: uma investigação dos conhecimentos docentes - Ruz, Maria Teresa Merino (2022)
This work presents the results of a qualitative research aimed at investigating, considering Shulman's theory categories (1987), the mathematics teaching knowledge associated with primary school teachers from a private school of São Paulo, having as a scenario the insertion of digital technologies in teaching processes in this segment. In addition to Shulman’s concepts, our theoretical references explore ideas from a scheme known as Technological Pedagogical Content Knowledge (TPACK), especially those that propose a conceptual framework for educational technology in integration with its didactic and content equivalents, in other terms, a conception that integrates those three aspects. One of the contexts that generated this investigation were situations that involved the student’s assessment, in which teachers exposed and discussed conceptions regarding mathematical knowledge. Subsidiarily, a survey about the unknowns regarding the teaching knowledge of those teachers, with no specific degree in Mathematics, was carried out. It was noted that there was little research that brought together all the variables that we did, however, such theoretical bases significantly contributed to the delimitation of our investigative fulcrum and to the expansion of concepts, such as “fluency”, for example, described by Oliveira (2018). To answer the raised questions, a questionnaire was used as a methodological instrument whose answers showed what the subjects consider as a challenge, when it comes to mathematics teaching and the use of digital technologies. The results showed that these teachers lack mathematical knowledge and that compromises their use of digital technologies to teach mathematics in the early years. Also, that they are aware of their weaknesses in the proper use of technological resources, claiming that they do not feel prepared to research, plan and develop work with students with autonomy, pointing out specialization courses that would fill in this gap